2017
DOI: 10.1175/jhm-d-16-0246.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods to Estimate Snow Water Equivalent at the Mountain Range Scale: A Case Study of the California Sierra Nevada

Abstract: Despite the importance of snow in global water and energy budgets, estimates of global mountain snow water equivalent (SWE) are not well constrained. Two approaches for estimating total range-wide SWE over Sierra Nevada, California, are assessed: 1) global/hemispherical models and remote sensing and models available for continental United States (CONUS) plus southern Canada (CONUS+) available to the scientific community and 2) regional climate model simulations via the Weather Research and Forecasting (WRF) Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 100 publications
5
82
0
1
Order By: Relevance
“…Peak mountain SWS from our estimate is 2.94 times greater than the CanSISE mountain estimate. Comparison of WRF with CanSISE over the mountains shows that current global models often have a large negative bias in mountain snow, consistent with previous studies (e.g., Dutra et al, ; Kapnick et al, ; Snauffer et al, ; Wrzesien et al, ). This difference is substantial; incorrect estimates of snow accumulation lead to incorrect water budgets, which preclude accurate description of the water cycle itself (Rodell et al, ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Peak mountain SWS from our estimate is 2.94 times greater than the CanSISE mountain estimate. Comparison of WRF with CanSISE over the mountains shows that current global models often have a large negative bias in mountain snow, consistent with previous studies (e.g., Dutra et al, ; Kapnick et al, ; Snauffer et al, ; Wrzesien et al, ). This difference is substantial; incorrect estimates of snow accumulation lead to incorrect water budgets, which preclude accurate description of the water cycle itself (Rodell et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Most striking, the WRF mountain estimate is nearly identical to the total continental storage in CanSISE (1,006 km 3 in WRF versus 1,087 km 3 in CanSISE), despite mountains covering ~25% of the total continent. Previous studies indicated that coarse‐resolution models like ERA‐Interim, a component of CanSISE, fail to capture snow accumulation in mountain regions (Ikeda et al, ; Kapnick & Delworth, ; Pavelsky et al, ; Snauffer et al, ; Wrzesien et al, ), so the low estimate from CanSISE, produced at 1°, is not surprising.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We dynamically downscale these events, using nested WRF simulations at 27, 9, and 3 km forced by the ERA‐Interim reanalysis, to examine extreme precipitation and other relevant fine‐scale thermodynamic and kinematic quantities event by event. Previous studies suggest resolutions of 10 km are needed to capture realistic orographic precipitation processes in mountainous regions (Minder et al, ; Pavelsky et al, ; Rasmussen et al, ; Wrzesien et al, ). Our results reinforce these earlier findings but also provide substantial additional insights into the importance of fine spatial resolution in the representation of precipitation and water vapor transport extrema—as well as resolution‐dependent drivers in topographically complex regions.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the spatial resolution of the WRF outputs, they used the MICROMET model (Liston and Elder, 2006b), a submodel of SnowModel in which WRF outputs are interpolated to a new grid, and then corrected physically according to topography. Wrzesien et al (2017) tested the capability of WRF to estimate SWE over complex terrain concluding that WRF simulations can be used over areas with few observational data.…”
Section: Introductionmentioning
confidence: 99%